Smartphone Application for Self Blood Glucose Monitoring & Disease Management- A Case Report - Kamar, Moshe (EAI Endorsed Transactions on Smart Cities, 2015)
Self-management of blood sugar glucose, diet and control of daily activities are crucial in overall management of type 2 diabetes mellitus (DM). In order to better adjust insulin type and dosage, educate for better diet patients are seldom requested to conduct a diary of their glucose measurements and meals. In today’s era of smartphone widespread use, it has been suggested that using mobile technology for self-blood glucose measurement together with the ability to automatically capture other factors important to control DM, may be an important method for enhancing disease self-management. The Dario™ device and mobile application, is a self-blood glucose monitoring device using smartphone interface. The application accumulates data of measurements, insulin intake, meals and physical activity. Users are also members of an electronic DM support group. We present a case of a 55 y.o. type 2 DM patient who reported using the device over a year period. The patient baseline HbA1c before using the Dario program was 7.4. He started using the Dario device and application and over a period of one year he managed to gradually reduce HbA1c to 6.2 by keeping his glucose measurements in range from 20% a week to 100%.